Collins Atlas of the World - Published by William Collins Sons & Co (London Collins, 1983)
Now revised and updated for 1995, a reference atlas of the world which includes a section on such topics as earthquakes, volcanoes, climate, vegetation, population and energy, information on all the world's nations, and a 40,000-name index (with latitudes and longitudes).
Include Color Illustration, Index and Glossary
Keywords: Atlases, British -- Atlases -- Geography